Effects of dietary polyunsaturated fatty acid on reproduction and developmental biology of Gangetic Mystus (Mystus cavasius) (Hamilton-Buchanan, 1822) - Akter, Rafia; Ema, Noore Safa; Hossain, Md Saddam; Hossain, Zakir (Asian Journal of Medical and Biological Research, 2021)
The present study was undertaken to determine the effects of polyunsaturated fatty acids (PUFAs) on enhanced maturation, spawning, embryonic and larval development of endangered Gangetic Mystus (Mystus cavasius). Fishes were collected from the Brahmaputra River, Mymensingh, Bangladesh and stocked in the cisterns. Treated group was provided supplemental diet enriched with 1% squid extracted lipids as a source of PUFAs four months whereas controlled group fed the same diet except PUFAs. In comparison with the control group, treated group exhibited higher reproductive performances in spawning trial. The fertilization rate (79.5±1.49), hatching rate (72.29±1.78) and survival rate (64.31±0.48) of offspring were significantly higher in treated group compared to control. Consequently, early embryonic and larval development was observed in the treated fishes. Therefore, the present study indicates the enhanced reproductive and developmental performances of (Mystus cavasius) owing to PUFAs supplementation in diet. Asian J. Med. Biol. Res. December 2020, 6(4): 641-649